Del sistema preposicional latino al caos preposicional castellano - Juliá, Tomás Jiménez (Rome and Iberia : Inspirations and Connections throughout History, 2021)
In Late Latin and the early stages of Castilian, prepositions assumed a role that they did not have in Classical Latin; namely, the identification of the case marks of the now disappeared flexional case system. This new role led to the grammaticalisation of the most commonly used prepositions and, thus, the progressive disappearance of the systematic set of semantic oppositions of Latin. The highly systematic set of prepositions was superseded by a chaotic collection of prepositional items in Spanish.